Bank competition and financial stability in Asia Pacific - Fu, Xiaoqing (Maggie); Lin, Yongjia (Rebecca); Molyneux, Philip (Journal of Banking & Finance, 2014)
Analysis of the tradeoff between competition and financial stability has been at the center of academic and policy debate for over two decades and especially since the 2007–2008 global financial crises. Here we use information on 14 Asia Pacific economies from 2003 to 2010 to investigate the influence of bank competition, concentration, regulation and national institutions on individual bank fragility as measured by the probability of bankruptcy and the bank’s Z-score. The results suggest that greater concentration fosters financial fragility and that lower pricing power also induces bank risk exposure after controlling for a variety of macroeconomic, bank-specific, regulatory and institutional factors. In terms of regulations and institutions, the results show that tougher entry restrictions may benefit bank stability, whereas stronger deposit insurance schemes are associated with greater bank fragility.